Which women uses social Internet networks during pregnancy? - Viaux-Savelon, Sylvie; Fouillet, Catherine; Bodeau, Nicolas; Nizard, Jacky (Clinical Journal of Obstetrics and Gynecology, 2021)
Internet has become an important part of our life, including during pregnancy where it is broadly used to find information (84%). The aims of this study were (1) to describe the proportion of women using Internet Social Networks (ISN) concerning their pregnancy, during pre or postpartum hospital stay, (2) to define how ISN users refer to their pregnancy and delivery on these social networks, (3) to compare anxiety level, social sustain level, sociodemographic characteristics of the both population (4) and to determine profiles of the ISN users with multiple correspondence analysis. Methods: 399 questionnaires were distributed in the postpartum wards of two academic hospitals in Paris, and 258 fully filled were retrieved. Tools: Anxiety scale (STAI- A and B), Cutrona Social Provisions Scale, sociodemographic and obstetrical questionnaire. Results: 76% (n = 195) were ISN users. We compared ISN users versus ISN non users women. Demographically, the two populations were comparable. Anxiety scores were similar in both groups, whereas social support scores showed a statistical difference in social integration. In the global population, 84% use Internet for information concerning pregnancy; this rate is higher for ISN users than ISN non users (tendency 0.058). ISN were used in priority for sharing with relatives, and 10% with other pregnant women. Concerning pregnancy, patients posted in priority the birth announcement (28%), the pregnancy announcement (23%), and the newborn’s pictures (12%). 6% posted their fetuses’ ultrasound pictures. Three clusters of ISN users were extracted with statistically different social support scores (p = 0.019) and comparable anxiety scores. The third one, with at risk profile, used ISN as social support. For all women, but specifically for younger and more socially fragile women, Internet gives to professional new perspectives to develop information and prevention tools during the perinatal period.